Contemporary women prisoners health experiences, unique prison health care needs and health care outcomes in sub Saharan Africa: a scoping review of extant literature. - Marie Claire Van Hout; Rosemary Mhlanga-Gunda (BMC, 2018)
Abstract Background Sub Saharan African (SSA) prisons have seen a substantial increase in women prisoners in recent years. Despite this increase, women prisoners constitute a minority in male dominated prison environments, and their special health needs are often neglected. Research activity on prison health remains scant in SSA, with gathering of strategic information generally restricted to infectious diseases (human immunodeficiency virus infection HIV/tuberculosis TB), and particularly focused on male prisoners. Health care provisions for women (and pregnant women) in SSA prisons are anecdotally reported to fall far short of the equivalence care standards mandated by human rights and international recommendations, and the recent agreements set out in the Southern African Development Community (SADC) Minimum Standards for HIV in Prisons. Methods A scoping review mapped what is currently known about women prisoners' health experiences, unique prison health care needs and health care outcomes in SSA. A systematic search collected and reviewed all available and relevant published and grey literature (2000-2017). Following removal of duplicates and application of exclusion measures, 46 records remained, which represented 18 of the 49 SSA countries. These records were subsequently charted and thematically analysed. Results Three themes were generated; 'The Prison Regime'; 'Navigating inside the Prison Health Infrastructure' and 'Accessing the outside Community and Primary Care Health Services'. Women in SSA prisons experience the same substandard nutrition, overcrowding and unhygienic conditions which exacerbate poor health and infectious disease transmission as males. Human rights abuses, substandard prison conditions and poor access to prison based and community clinical care, along with the invisible nature of women and that of their unique health needs are deplorable. Conclusions The review has highlighted the dearth of gender specific strategic information on women prisoners in the region, appalling environmental conditions and prison health care provision, and violation of human rights for those incarcerated. Enhanced donor support, resource allocation, prison health and population health policy reform, health systems surveillance and gender sensitive prison health service provision is warranted. This will help address women prisoners' conditions and their specific health needs in SSA prisons, and ultimately bridge the gap between prison and population health in the region.